A Review on Electrochemical and Photochemical Processes for Hydrogen Production. Issue 5 (3rd September 2022) - Parangi, Tarun
ABSTRACT: Hydrogen (H2 ) is examined as a fuel and as one of the most extensively studied substitute energy resources for available sources that are being consumed rapidly. Thus, the growing interest in the development of competitive, low-cost hydrogen production leads us to devote particular efforts to establish efficient processes in an economical and environmentally benign way. In this view, both photochemical and electrochemical processes have been exclusively investigated as greener paths for hydrogen production. The present review article highlights the process established for hydrogen generation over the last few years. The overall thrust of the present theme is a discussion of the efforts that have been made so far for finding hydrogen as an alternative fuel from different feedstock through photochemical and electrochemical processes.